Polysiloxane–poly(vinyl alcohol) composite dielectrics for high-efficiency low voltage organic thin film transistors. Issue 16 (4th April 2019) - Cao, Jupeng; Wei, Xiaoyun; Che, Yuxuan; Li, Aiyuan; He, Yaowu; He, Chao; Zhu, Yanan; Chen, Xiaolong; Li, Tingting; Murtaza, Imran; Yan, Lijia; Perepichka, Dmitrii F.; et al.
Abstract : The strategy of composite polymer dielectrics for low consumption-high efficiency organic thin film transistors via the solution method. Abstract : The gate dielectric layer is one of the important components in organic thin film transistors (OTFTs) which affects the charge mobility, power consumption and stability of the device. Here, we report new composite polymer dielectrics prepared by sol–gel chemistry from commercial siloxanes and poly(vinyl alcohol), featuring a high dielectric constant ( k ∼ 8–16) and hydrophobicity. OTFTs fabricated with the developed polymer dielectric exhibit ultra-low driving voltage (<3 V), extremely high charge mobility (up to 6 cm 2 V −1 s −1 for pentacene and up to 50 cm 2 V −1 s −1 C8-BTBT), negligible hysteresis and excellent operational stability. This is an important step towards the practical realization of low-cost p-type OTFTs.